The Role of Financial Statements for Culinary SME’s in Jakarta - Pujiastuti, Heni (Dinasti International Journal of Digital Business Management, 2023)
The role of financial statements as a measure of a company's performance is very necessary. Through this important role, this research was conducted with the hope of providing input to all businesses, especially Medium, Small and Independent Enterprises (MSMEs) in Jakarta, the variables used in this study include Financial Literacy, Financial Understanding, Motivation for Preparing Financial Statements and Applying Financial Statements. This study sample used 65 culinary businesses in the Jakarta area. Quantitative methods are used in the analysis of data obtained through interviews and questionnaires which are further processed using Smart Partial Least Squares 4. The test results illustrate that financial literacy has an influence on the understanding of business people in financial management, improving the ability of business people to manage finances and the ability to compile a financial report.